DETERMINATION OF REQUIRED STRENGTH OF MDF BLANK FINGER JOINT - Koval, Lyubomyr; Udovytskyy , Oleksandr (Forestry, Forest, Paper and Woodworking Industry, 2024)
The main areas of application of MDF linear elements are analyzed; techniques for determining required strength of MDF blank finger joint have been devised; shown here are a Linear-element load diagram and a shear-and-bending moments diagram; a relationship between a breaking and design bending moments is specified; also, a required relative strength of MDF linear-element finger joint has been determined.